PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MOBILE PADA MATA PELAJARAN ADMINISTRASI SISTEM JARINGAN DI SMKN 1 TANJUNG RAYA - Muhammad Iqbal; Faiza Rini; Haris Kurniawan (STMIK KAPUTAMA, 2023)
The purpose of this study is to produce valid learning media in the subject of Network Systems Administration at SMKN 1 Tanjung Raya. Type of research conducted This research uses research and development (R&D) methods with a development model. Development has the ADDIE research model because the product being developed is learning media not software engineering, so the ADDIE model is suitable for the product development process. research results and discussion of the development of mobile-based learning media in the subject of Network System Administration at SMKN 1 1 Tanjung Raya. The validity test of mobile-based learning media was carried out by 3 validators, namely the media validator and material validator, for media validators it was carried out by 3 lecturers, while Material control was carried out by 1 lecturer and 2 teachers who taught Network System Administration at SMKN 1 Tanjung Raya. The validity for media experts is 91,67% with a valid category, material validity is 92% with a valid category.